Survey of Inmates in Local Jails, 1996: (United States) ([Verlag nicht ermittelbar], 1999)
This collection provides nationally representative data on persons held prior to trial and on convicted offenders serving sentences in local jails or awaiting transfer to state prisons. Data cover demographic characteristics of jail inmates (sex, race, ethnicity, Hispanic origin, employment), current offenses and sentences, detention status, trial, bail, characteristics of victims, criminal histories, incident characteristics, socioeconomic circumstances, jail conditions and activities, and prior drug and alcohol use and treatment. Part 1, Numeric Data, contains numeric data for all questions in the survey, while Part 2, Alphanumeric Data, consists of nonnumeric answers to the "Other, Specify" selection available for some of the questions.